High flux membrane based on in-situ formation of zirconia layer coated the polyethersulfone substrate for ions separation - Chabi Noël Worou (IWA Publishing, 2021)
A flawless, extremely loose, membrane, efficient for multivalent ions separation, has been successfully synthesized by the in-situ formation approach. The as-synthesized nanofiltration (NF) membrane, NF_PES-Zr, proceeded from a thin film layer of nanoparticles (NPs) zirconium that coated the platform of the polyethersulfone (PES) ultrafiltration (UF) membrane through a bio-glue made from dopamine hydrochloric and sodium bicarbonate buffer. The estimation of the average pore size of the novel organic-inorganic NF membrane NF_PES-Zr using the filtration velocity approach of Guerout-Elford-Ferry was close to 0.9 nm. NF_PES-Zr membrane holds a record in permeate water flux release of about 62.5 and was revealed to be effective for multivalent ions separation. A 5 days-test performed on NF_PES-Zr demonstrated its long-term stability and showed a rejection rate of 93.4% and 37.8% respectively for and . HIGHLIGHTS Organic-inorganic membrane preparation.; Nanoparticle zirconium deposition by in-situ formation method.; Modification of an ultrafiltration membrane to a nanofiltration membrane.; Energy dispersive spectrometry (EDS) associated with field emission scanning electron microscopy (FESEM) for membrane surface structures characterization.; High flux membrane for ions separation.;